Metaphor and space - FRENDA, ALESSIO SALVATORE (Trinity College Dublin, 2005)
The present research study aims at providing an insight on the issue of metaphor and space conceptualization through the comparative analysis of Irish and Italian prepositions, based on the theoretical foundations of cognitive linguistics, an insight into which was provided in the form of a literature review. In order to pursue this end, two distinct corpora were set up for the two languages by drawing textual strings containing instances of morphologically simple prepositions. Subsequently, it was illustrated how simple prepositions, both in Irish and Italian, primarily express relations of a spatial kind. Once this was done, prepositions were grouped together according to their basic spatial meaning (BSM), and three such BSMs were chosen for being analyzed cross-linguistically with respect to their nonspatial readings, which were shown to be linked to their spatial meanings by means of metaphorical mapping of conceptual structure, according to the expectations that the theoretical background adopted would engender.
A cognitive-based analysis of Irish and Italian prepositions
APPROVED
Keywords: linguistics; metaphor; space conceptualization; Irish; Italian; prepositions; cognitive linguistics